Heads or tails? Structural events and molecular mechanisms that promote mammalian sperm acrosomal exocytosis and motility - Buffone, Mariano Gabriel (2012)
Sperm structure has evolved to be very compact and compartmentalized to enable the motor (the flagellum) to transport the nuclear cargo (the head) to the egg. Furthermore, sperm do not exhibit progressive motility and are not capable of undergoing acrosomal exocytosis immediately following their release into the lumen of the seminiferous tubules, the site of spermatogenesis in the testis. These cells require maturation in the epididymis and female reproductive tract before they become competent for fertilization. Here we review aspects of the structural and molecular mechanisms that promote forward motility, hyperactivated motility, and acrosomal exocytosis. As a result, we favor a model articulated by others that the flagellum senses external signals and communicates with the head by second messengers to affect sperm functions such as acrosomal exocytosis. We hope this conceptual framework will serve to stimulate thinking and experimental investigations concerning the various steps of activating a sperm from a quiescent state to a gamete that is fully competent and committed to fertilization. The three themes of compartmentalization, competence, and commitment are key to an understanding of the molecular mechanisms of sperm activation. Comprehending these processes will have a considerable impact on the management of fertility problems, the development of contraceptive methods, and, potentially, elucidation of analogous processes in other cell systems.